'At 20p – It Can't be Bad!': The socio-political purpose of Live Theatre Newcastle's amateur aesthetic, 1973–8. (2nd January 2020) - Haslett, Rosalind
Abstract : Live Theatre Newcastle was established as a working-class collective in 1973 in order to make theatre about 'life as ordinary working people live it'. In this essay, I argue that Live Theatre self-consciously developed an amateur aesthetic in its early years (1973–8) by using self-deprecating jokes and highlighting the low cost and low production values of its own work. The cultivation of this amateur aesthetic was useful to the company because it allowed for a radical reimagining of the performer–audience relationship that was both politically purposeful as a form of participatory democracy and also alert to issues of class. The essay draws upon materials from the Live Theatre Archive, which was accessioned to Newcastle University in 2017, and supplements these with ethnographic and conversation-based research with early company members. I argue that the amateur aesthetic developed by Live Theatre during these years was a socio-political strategy designed to engage audiences actively and ideologically, but also with sensitivity and respect.